EVALUATING THE EFFECTS OF NEEM COATED UREA AND MORINGA LEAF EXTRACTS ON GROWTH AND YIELD OF MAIZE (Zea mays L.) - Ashiru, A.A.; Rufa’i, S.; Gambo, U.; Umar, S.U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the individual and combined effects of Neem Coated Urea (NCU), a slow-release nitrogen source, and Moringa Leaf Extract (MLE), a natural biostimulant, on the growth and yield of maize during the 2024 rainy season at two locations in Kano State, Nigeria. The treatments comprised of five levels of nitrogen source (0%, 75%, 100%, 125% NCU, and conventional Urea) and four levels of foliar-applied MLE (0%, 5%, 7%, and 9%). These were factorially combined and laid out in a Randomized Complete Block Design (RCBD) with three replications. Results of the experiment showed that both NCU and MLE significantly enhanced all measured growth parameters, including plant height, leaf area, total dry weight, and chlorophyll content, compared to the control and conventional urea. NCU, particularly at the 125% application rate, consistently produced the highest values for vegetative growth and yield components. Similarly, the 9% MLE concentration resulted in the most significant improvements in plant performance. The highest yield was achieved with the combined application of 125% NCU and 9% MLE. This combination significantly outperformed conventional urea, demonstrating the superior efficiency of NCU in reducing nitrogen losses and the complementary role of MLE in stimulating plant metabolism and nutrient uptake. The study concludes that integrating Neem Coated Urea with foliar Moringa Leaf Extract is a highly effective and sustainable strategy for maximizing maize productivity in the Sudan Savanna. Farmers in the region are recommended to adopt the application of 125% NCU combined with 9% MLE for optimal maize production.